The Dream Maker: Significant Spaces in El movimiento y el sueño by Alejandro Romualdo - Lindo Pablo, Cristian Walter (2021)
This work proposes a new interpretation of one of the most important poetry books of Romualdo’s work: El movimiento y el sueño [The movement and the dream]. A work where the author consolidates the main objective of his poetic work: the constant search for a new poetic reality by working tenaciously and incisively on the materiality of language. To this end, after a review of the various stages of his work and the meager criticism of his poetics, the collection is analyzed from the conception of concrete poetry proposed by the Noigandres Group, and then the poem is analyzed from the notion of dream and spatial relationships proposed by Lotman and Freud’s notion of condensation.